The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.2478/v10026-008-0025-3
|View full text |Cite
|
Sign up to set email alerts
|

Production of organic fertilizer from poultry feather wastes excluding the composting process

Abstract: Chicken feathers generated in large quantities by the poultry industry are hazardous for the natural environment because of their poor digestibility and their potential as a source of microbiological pathogens. Currently, the main method of feather waste management is the production of feather meal by steam pressure cooking. This technology requires a high energy input. The high costs of hydrothermal degradation of these wastes are conducive to finding other alternative possibilities of poultry wastes manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…The pH is one of the important characteristics of the composting process; the chicken feathers' compost was highly alkaline (pH > 8.60). The chicken feathers composting occurs in a strongly alkaline 8.37 ± 1.33 b 1.55 ± 0.87 c 6.35 ± 0.04 c 0.15 ± 0.08 c 3.62 ± 1.52 c 16.80 ± 1.92 b 1.40 ± 0.94 e 0.51 ± 0.14 c 6.62 ± 1.12 c environment during the process which causes the inactivation of the pathogens in the feathers compost (Tronina and Bubel 2008). The maximum available nitrogen content in E 2 was 7.33%, which is consistent with the findings of Jeong et al 2010.…”
Section: Resultsmentioning
confidence: 99%
“…The pH is one of the important characteristics of the composting process; the chicken feathers' compost was highly alkaline (pH > 8.60). The chicken feathers composting occurs in a strongly alkaline 8.37 ± 1.33 b 1.55 ± 0.87 c 6.35 ± 0.04 c 0.15 ± 0.08 c 3.62 ± 1.52 c 16.80 ± 1.92 b 1.40 ± 0.94 e 0.51 ± 0.14 c 6.62 ± 1.12 c environment during the process which causes the inactivation of the pathogens in the feathers compost (Tronina and Bubel 2008). The maximum available nitrogen content in E 2 was 7.33%, which is consistent with the findings of Jeong et al 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the liquid waste is generally directly discharged into the sewerage. Contrary to this fact, Tronina and Bubel (2008) and Okanovic et al (2009) reported that the wastewater produced from poultry slaughterhouse containing 0.5-9.0% macro and micro nutrients, 11.0-15.2% organic carbon (C-organic), as well as 0.15-13.6% of amino acid substances. Likewise, the alimentary tracts which may contain up to 80% of total undigested substrates is a potential source to be utilized as organic fertilizers (Chojnacka et al, 2006;Kivela et al, 2009;Leon et al, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…These wastes are often processed into valuable products such as feed and fertilizer (Veerabadran et al, 2012;Stingone and Wing, 2011). Uncontrolled waste disposal contributes to environmental damage and disease transmission (Tronina and Bube, 2008) and also potentially as a source of harmful arsenic toxins if not managed properly (Nachman et al, 2012). The poultry waste management system through the combustion process can have an impact on the environment (Nachman et al, 2005;.…”
Section: Introductionmentioning
confidence: 99%